Norursodeoxycholic acid versus placebo in the treatment of non-alcoholic fatty liver disease: a double-blind, randomised, placebo-controlled, phase 2 dose-finding trial. (October 2019) - Traussnigg, Stefan; Schattenberg, Jörn M; Demir, Münevver; Wiegand, Johannes; Geier, Andreas; Teuber, Gerlinde; Hofmann, Wolf Peter; Kremer, Andreas E; Spreda, Frank; Kluwe, Johannes; Petersen, Jörg; Boettler, Tobias; et al.
Summary: Background: Norursodeoxycholic acid is an orally administered side chain-shortened homologue of ursodeoxycholic acid that undergoes hepatic enrichment with hepatoprotective, anti-inflammatory, and antifibrotic activity. We assessed the efficacy of two doses of norursodeoxycholic acid versus placebo for the treatment of non-alcoholic fatty liver disease. Methods: We did a multicentre, double-blind, placebo-controlled, randomised, phase 2 dose-finding clinical trial in tertiary referral hospitals and medical centres in Austria (n=6) and Germany (n=23) for patients with non-alcoholic fatty liver disease with or without diabetes. Patients with a clinical diagnosis of non-alcoholic fatty liver disease and serum alanine aminotransferase (ALT) concentrations of more than 0·8 times the upper limit of normal were randomly assigned (1:1:1) using a computer-generated central randomisation. Patients were randomly assigned to receive either norursodeoxycholic acid capsules at 500 mg per day or 1500 mg per day, or placebo, for 12 weeks with a subsequent 4-week follow-up period. All individuals involved in the trial were masked to treatment allocation. The primary efficacy endpoint was the mean relative percentage change in ALT concentrations between baseline and end of treatment assessed in the intention-to-treat population. This trial is registered with EudraCT, number 2013-004605-38. Findings: Between March 30, 2015, and Sept 20, 2016, of 198 individuals included in the analysis, 67 patients were randomly assigned to receive 500 mg norursodeoxycholic acid, 67 to 1500 mg norursodeoxycholic acid, and 64 to placebo. A dose-dependent reduction in serum ALT between baseline and end of treatment was observed with norursodeoxycholic acid versus placebo, with a significant effect in the 1500 mg group (mean change −27·8%, 95% repeated CI −34·7 to −14·4; p<0·0001). Serious adverse events (n=6) and treatment-emergent adverse events (n=314) were reported in a similar proportion of patients across groups. 112 treatment-emergent adverse events occurred in the 1500 mg group, 99 in the 500 mg group, and 103 in the placebo group. The most frequent adverse events were headache, gastrointestinal disorders, and infections (eg, diarrhoea, abdominal pain, or nasopharyngitis). Interpretation: Norursodeoxycholic acid at 1500 mg resulted in a significant reduction of serum ALT within 12 weeks of treatment when compared with placebo. Norursodeoxycholic acid was safe and well tolerated encouraging further studies. Funding: Dr Falk Pharma GmbH.